Membumikan Kebinekaan Bangsa Indonesia Melalui Pendidikan Pluralisme dan Multikulturalisme - Laras Prastyani, Kinanti (Hawari: Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
Pluralism and multiculturalism education are two things that are very important in the education of the Indonesian nation today. This research was conducted to analyze the impacts that occur due to the lack of pluralism and multiculturalism education that is poorly understood by some Indonesian people and how to continue to ground the diversity of the Indonesian nation amid the influence of existing pluralism and multiculturalism conflicts. Basically, these conflicts are present due to the lack of understanding of some Indonesian people about pluralism and multiculturalism education in Indonesia and cause impacts that can still be sought for solutions. For example, such as religious conflicts and cultural conflicts that occur in Indonesia, many are not responsible for the presence of these conflicts. The lack of public attention about plural and multicultural education and the lack of understanding of the community about how to solve conflict problems that occur is also a trigger for the presence of these conflicts. In this research, the author uses the Library Research method, namely the analysis and collection of data on journals or articles, books and internet searches recognizing the theme of the author's research in order to get references and conclusions, the results of which the author is able to make efforts to deal with and anticipate problems or impacts that occur due to conflicts of lack of knowledge about pluralism and multiculturalism education so that we as the younger generation of the nation's successors can still ground the diversity of the Indonesian state which characterizes our beloved country